Synthesis and characterization of new class of geopolymer hybrid composite materials from industrial wastes - Thakur, Anil Kumar; Pappu, Asokan; Thakur, Vijay Kumar (Elsevier, 2019)
Geopolymer belongs to a new class of emerging materials for a number of applications owing to the advantages such as low cost; higher compressive strength; improved fire & acid resistance as well as reduced greenhouse gas emission. In this work, we explore the effective utilization of marble waste as a reactive filler and binder for the development of fly ash based geopolymer hybrid composite materials using extrusion process. The effect of marble waste content on the physico–chemical and mechanical characteristics of prepared hybrid materials was studied through various characterization techniques. The geopolymerization was conducted at two different molarities of sodium hydroxide in which the effects of materials properties were studied. The results indicate that the materials prepared at higher molarity exhibits better performance in terms of compressive strength (4.61–6.52 MPa) (2–4M). The silicon dioxide present in fly ash reacts with calcium hydroxide present in marble waste forming calcium silicate hydrate network and possibly contributes to the increment in the interfacial bonding in marble waste infiltrated geopolymer matrix. Overall, this improved interfacial adhesion yielded an increase in compressive strength and bulk density but also decreased the water absorption of the developed material. The results of this study not only indicate an effective utilization of marble waste for the production of geopolymer hybrid composite materials via an eco–friendly route but also provide an economical and sustainable route for management of marble waste currently generated in various countries of the world.
Keywords: Geopolymer; Hybrid materials; Marble waste; XRD; SEM; TGA; Mechanical characterization